Enzymatic degradation of polyurethanes. Part I. Decomposition products evaluation and mathematical modeling of process - Wojturska, J. (Polimery, 2011)
This paper constitutes a presentation of the factors influencing the enzymatic hydrolysis of polymers, the corresponding degradation mechanism and also a review of the literature regarding enzymatic degradation of polyurethanes (PUR) in general. Studies on the separation and identification of PUR degradation products released as a result of enzyme activity have been presented. Moreover, the literature regarding the mathematical aspects of degradation process was reviewed. The development of such a model for the in vitro enzymatic degradation of PUR is essential in understanding the kinetics of the process and enable the prediction of polymer behavior in vivo.